Legal Analysis of the Reduction in Scope and Transfer of Agreement in Toll Road Concessions Between the Old Toll Road Business Entity and the New Toll Road Business Entity - Muzammil Hidayat; Yusup Hidayat (Journal of Social Research, 2025)
Toll road concession agreements in Indonesia often face complex dynamics requiring contractual adjustments between Toll Road Business Entities (BUJT) and the government. A significant legal issue arises when Old BUJTs fail to fulfill their obligations, necessitating scope reduction and subsequent transfer to New BUJTs. This process creates substantial legal uncertainties regarding the validity of the agreement post-amendment, proper mechanisms for scope reduction, and protection of the rights and obligations of all parties involved. Currently, no clear legal framework governs this mechanism, leading to ad hoc decisions that generate legal uncertainty for both Old and New BUJTs and potentially hinder the sustainable development of toll road infrastructure. This research employs a juridical-normative approach to comprehensively analyze the legal problems arising from the reduction of toll road business scope. It evaluates existing legal foundations and identifies ideal mechanisms to ensure legal certainty. The study's novelty lies in its specific focus on scope reduction as a distinct legal mechanism under the new regulatory framework of Law Number 6 of 2023 and Government Regulation Number 23 of 2024. The research implications provide crucial recommendations for developing detailed technical guidelines for scope reduction implementation, strengthening mediation and arbitration mechanisms in concession agreements, and establishing fair compensation frameworks. These findings are expected to contribute significantly to the improvement of toll road business regulations in Indonesia and to strengthening more transparent, fair, and sustainable infrastructure governance.